2014
DOI: 10.1186/1471-2431-14-234
|View full text |Cite
|
Sign up to set email alerts
|

"Are you available for the next 18 months?" - methods and aims of a longitudinal birth cohort study investigating a universal developmental surveillance program: the ‘Watch Me Grow’ study

Abstract: BackgroundUniversal developmental surveillance programs aimed at early identification and targeted early intervention significantly improve short- and long-term outcomes in children at risk of developmental disorders. However, a significant challenge remains in providing sufficiently rigorous research and robust evidence to inform policy and service delivery. This paper describes the methods of the ‘Watch Me Grow’ study that aims to maximise accurate early detection of children with developmental disorders thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 33 publications
0
41
0
Order By: Relevance
“…The birth cohort was followed with telephone interviews at 6, 12 and 18 months of age. The WMG study protocol has been previously reported 17. Information about screen time was collected at the 18-month follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…The birth cohort was followed with telephone interviews at 6, 12 and 18 months of age. The WMG study protocol has been previously reported 17. Information about screen time was collected at the 18-month follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…The ‘Watch Me Grow’ (WMG) study was designed to evaluate the feasibility, accuracy, barriers and enablers of the current developmental surveillance systems in South Western Sydney—an area of significant social disadvantage located about 35 km from the Sydney central business district. 12 A key component of the WMG study was the establishment of a longitudinal birth cohort. The WMG study protocol, recruitment methods, representativeness and baseline risk factors have previously been reported.…”
Section: Methodsmentioning
confidence: 99%
“…These were a subsample of a birth cohort recruited for the ‘Watch Me Grow’ study, a mixed methods study of developmental risk and surveillance in NSW. Recruitment methods have been detailed elsewhere (Eapen et al ; Woolfenden et al ). Participants who had completed the first two study components (baseline and 6‐month follow‐up) at the time of analysis were selected for inclusion.…”
Section: Methodsmentioning
confidence: 99%
“…Child developmental problems represent an ever increasing health and economic concern (Jarbrink et al 2003;Matson & Kozlowski 2011;Lavelle et al 2014). While early intervention may reduce the impact of developmental disorders (McConachie & Diggle 2007;Rogers & Vismara 2008;Howlin et al 2009;Einfeld et al 2013), timely identification of children who could benefit remains a significant challenge (Chung et al 2006;Eapen et al 2014).…”
Section: Introductionmentioning
confidence: 99%